(untitled) (Research, Society and Development, 2022)
The pequi, a yellow fruit native to the Brazilian Cerrado, has nutritional characteristics of great interest to the food industry. The present study aims to incorporate different concentrations of pequi flour into chicken burgers, evaluating its composition and its physical and technological properties. Therefore, analyses of centesimal composition, hydrogen potential (pH), water activity (Aw), instrumental color and texture and cooking loss (PPC) were performed. The parameters: water activity (Aw), adhesiveness, cohesiveness and flexibility did not present significant differences (p<0.05). The other parameters: pH, instrumental color, hardness, cooking loss and centesimal composition showed significant differences (p<0.05) between the analyzed treatments. The results showed that the addition of up to 3% of pequi flour resulted in chicken burgers with concentrations of lipids and carbohydrates within those established by the current legislation. As for the pH values, the results were proportional to the addition of pequi flour, however, the increasing in flour reduced the cooking loss of chicken burgers. In addition, the addition of pequi flour directly influenced the color of the hamburgers, that present intense shades of yellow and high hue. Considering the texture, the hardness parameter obtained low values indicating that the addition of pequi flour resulted in softer chicken burgers.